(untitled) (Scientific journal of the Fergana State University, 2024)
This article discusses the history of establishing cultural ties and modern development prospects between the Republic of Uzbekistan and the countries of Southeast Asia from 1991 to the end of 2019. In the first years of independence, good relations were established between the Republic of Uzbekistan and the countries of Southeast Asia, but in 2017 cooperation in the cultural sphere developed unsteadily. The current measures prove that countries have great potential and cooperation is mutually beneficial. Economic ties between Uzbekistan and the countries of Southeast Asia are studied on the basis of a comparative analysis of periods, changes, cooperation and problems between the two countries. On the basis of analytical views, the role of relationships in the spheres of economy and culture is revealed. The article indicates the achievements and problems in cooperation along these lines between Uzbekistan and the ASEAN member states. The novelty of the scientific article lies in highlighting the aspects of economic, cultural and humanitarian relations between Uzbekistan and the ASEAN countries in 1991-2019; efforts were made to identify the rich experience of the countries of Southeast Asia in this area and opportunities for cooperation; relations between Uzbekistan and the countries of Southeast Asia are unevenly developed; Uzbekistan did not maintain active relations with all the countries of the region.